C-reactive protein and mortality in mild to moderate chronic obstructive pulmonary disease. Issue 10 (31st May 2006) - Man, S F P; Connett, J E; Anthonisen, N R; Wise, R A; Tashkin, D P; Sin, D D
Abstract : Background: Although C-reactive protein (CRP) levels are increased in chronic obstructive pulmonary disease (COPD), it is not certain whether they are associated with adverse clinical outcomes. Methods: Serum CRP levels were measured in 4803 participants in the Lung Health Study with mild to moderate COPD. The risk of all-cause and disease specific causes of mortality was determined as well as cardiovascular event rates, adjusting for important covariates such as age, sex, cigarette smoking, and lung function. Cardiovascular events were defined as death from coronary heart disease or stroke, or non-fatal myocardial infarction or stroke requiring admission to hospital. Results: CRP levels were associated with all-cause, cardiovascular, and cancer specific causes of mortality. Individuals in the highest quintile of CRP had a relative risk (RR) for all-cause mortality of 1.79 (95% confidence interval (CI) 1.25 to 2.56) compared with those in the lowest quintile of CRP. For cardiovascular events and cancer deaths the corresponding RRs were 1.51 (95% CI 1.20 to 1.90) and 1.85 (95% CI 1.10 to 3.13), respectively. CRP levels were also associated with an accelerated decline in forced expiratory volume in 1 second (p<0.001). The discriminative property of CRP was greatest during the first year of measurement and decayed over time. Comparing the highest and lowest CRP quintiles, the RR was 4.03 (95% CI 1.23 to 13.21) for 1 year mortality, 3.30 (95% CI 1.38 to 7.86) for 2 year mortality, and 1.82 (95% CI 1.22 to 2.68) for ⩾5 year mortality. Conclusions: CRP measurements provide incremental prognostic information beyond that achieved by traditional markers of prognosis in patients with mild to moderate COPD, and may enable more accurate detection of patients at a high risk of mortality.